(untitled) (European Journal of Child Development, Education and Psychopathology, 2019)
Music has an intrinsic emotional component that makes it a universal language. All people react emotionally to music. This study aims to present the results of the validation of a test called EMU that measures the ability to identify emotions with fragments of classical music, in addition to measuring the perception of tempo and the intensity of music. The sample of the study is composed of 514 students from two universities in Spain and Bulgaria that cover several specialties. The results indicate a moderate reliability of the test as a whole (?= .60) and that the musical characteristics of intensity and tempo have a direct relationship with emotional identification although this is not significantly relevant. It can be concluded that part of the test, that of identifying emotions, is one that presents a high reliability (?= .71). Likewise, it is proposed that the rest of the parts continue to be explored.